2013
DOI: 10.1038/cgt.2013.35
|View full text |Cite|
|
Sign up to set email alerts
|

Combining CAR T cells and the Bcl-2 family apoptosis inhibitor ABT-737 for treating B-cell malignancy

Abstract: B-cell malignancies upregulate the B-cell lymphoma 2 (Bcl-2) family inhibitors of the intrinsic apoptosis pathway, making them therapy resistant. However, small-molecule inhibitors of Bcl-2 family members such as ABT-737 restore a functional apoptosis pathway in cancer cells, and its oral analog ABT-263 (Navitoclax) has entered clinical trials. Gene engineered chimeric antigen receptor (CAR) T cells also show promise in B-cell malignancy, and as they induce apoptosis via the extrinsic pathway, we hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…Clinical safety data from the performed trial showed that ABT-199 had modest impact on myelosuppression, except for grade 3–4 neutropenia in 41% of patients [42]. ABT-199 is an agent currently being investigated for the treatment of AML [27], and it would be interesting to use targeted therapy sequentially with CAR T-cells, in order to exert a synergistic effect on resistant leukemia clones [43]. We also added, at a similar concentration, the pan-BCL inhibitor ABT-737 which resulted in a potent lymphotoxic effect as well [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical safety data from the performed trial showed that ABT-199 had modest impact on myelosuppression, except for grade 3–4 neutropenia in 41% of patients [42]. ABT-199 is an agent currently being investigated for the treatment of AML [27], and it would be interesting to use targeted therapy sequentially with CAR T-cells, in order to exert a synergistic effect on resistant leukemia clones [43]. We also added, at a similar concentration, the pan-BCL inhibitor ABT-737 which resulted in a potent lymphotoxic effect as well [29].…”
Section: Discussionmentioning
confidence: 99%
“…CAR T-cell therapy was efficient in all lines tested, whereas ABT-737 only had a direct effect in some of them. However, when combined, the apoptosis level was greatly enhanced demonstrating that ABT-737 could sensitize the apoptosis machinery to extrinsic signalling from T-cells [62]. It should, however, be noted that resting T-cells are type I cells [30] and could be sensitive to ABT-737 themselves.…”
Section: Adjuvants For Car T-cell Therapymentioning
confidence: 96%
“…We therefore also investigated ABT-737 as a pre-sensitizer to CAR T-cell therapy. Although the strongest effect was seen with concomitant addition of ABT-737 and CAR T-cells, the effect of combination treatment was still enhanced when tumour cells were pre-sensitized with ABT-737 prior to addition of CAR T-cells [62]. Another approach of apoptosis inhibitor blockade is the use of IAP inhibitors.…”
Section: Adjuvants For Car T-cell Therapymentioning
confidence: 97%
“…Finally, incorporating chemokine or cytokine expression into the CAR-T-cell construct might improve delivery and trafficking of the cells to the tumour 42,43,82,83 . Combination treatment with small-molecule inhibitors, such as ibrutinib or lenalidomide, or with immune-checkpoint inhibitors can be explored to improve CAR-T-cell activation or suppress the endogenous T-cell-inhibitory microenvironment, which might enhance treatment efficacy 8486 .…”
Section: Engineered Car T Cellsmentioning
confidence: 99%